Association between urinary metal levels and slow vital capacity in Chinese preschoolers. Issue 5 (3rd July 2022) - Liu, Yang; Yu, Lili; Ji, Hongxian; Zhu, Meiqin; Liu, Yanli; Fu, Ye; Zhang, Yao; Li, Hongbo; Duan, Yanying; Ding, Hongcheng; Wang, Jing
Abstract: Objectives: Heavy metal exposure has been associated with lung function decline, but there is still a lack of evidence on preschoolers. In this study, we evaluated cross-sectional associations between urinary metal levels and slow vital capacity (SVC) in preschoolers. Methods: A total of 1284 children were selected from seven-kindergartens. Urinary concentrations of 23 metals were measured by inductively coupled plasma mass spectrometry. Utilized least absolute shrinkage and selection operator penalized regression was used to select the metals independently associated with SVC. Generalized linear models were used to evaluate the association between urinary metals level and SVC. Result: In the single-metal model, we observed negative associations between urinary aluminum, copper, zinc, rubidium, lead and SVC, comparing extreme quartiles the regression coefficients β (95% CI) were −41.01 (95% CI: −78.02, −4.01, P for trend = 0.029), −62.91 (95% CI: −99.85, −25.96, P for trend = 0.004), −33.48 (95% CI: −69.95, 3.00, P for trend = 0.042), −49.45 (95% CI: −86.10, −12.81, P for trend = 0.012) and −55.64 (95% CI: −91.88, −19.40, P for trend = 0.005), respectively. Urinary copper was negatively associated with SVC in boys, urinary zinc and lead were negatively associated with SVC in girls. Similar results were obtained in the multiple-metal model, the β for copper comparing extreme quartiles was −98.90 (-95% CI: −165.50, −32.29, P for trend = 0.006) in boys, the β for zinc and lead comparing extreme quartiles were −54.50 (95% CI: −107.60, −1.41, P for trend = 0.012), −84.32 (95% CI: −151.40, −17.24, P for trend = 0.016) in girls. Conclusions: The levels of urinary aluminum, copper, zinc, rubidium, lead were negatively associated with SVC in preschoolers. These associations were different between boys and girls. Further prospective and experimental studies are warranted to clarify the underlying mechanisms.